GE_GERICHTE C/9302/2012 vom 12. Juni 2013 - GE Cour de justice (2013)
BAIL À LOYER; LOYER; GESTION DE SINISTRES; COMPENSATION DE CRÉANCES; FARDEAU DE LA PREUVE; DOMMAGE | Cst.29.2; CPC.150.1; CPC.152.1; CO.259e